THE COMPARISON BETWEEN THE THERMAL PERFORMANCE OF A CONTEMPORARY HOUSE AND TRADITIONAL HOUSE IN THE DENSE DHAKA CITY IN BANGLADESH (DIMENSI: Journal of Architecture and Built Environment, 2013)
Bangladesh Traditional houses (B.T.H) which are located in warm humid tropical climate represent a unique phenomenon with device capable to meet the comfort demand through environmental well adapted design.  Recently the traditional house and the contemporary design house (C.D.H) for Bangladesh are examined by comparing the thermal performance within the same outdoor condition and the climatic region at the dense Dhaka city.  This comparison is based on field measurements of thermal performance of the traditional house and the contemporary design house within the same summer period. Quantitative method is used to measure the thermal performance. The field survey was conducted using two set of thermal data loggers were installed in both selected houses to record the air temperature and relative humidity of the outdoor and indoor spaces.  Data collection was carried out for the hot and wet month of summer period in June.  The research result concluded that the traditional houses of Bangladesh provided useful indicators of appropriate architectural design response to climate, particularly in the context of purely passive environmental control. However it is required to adapt a critical approach towards the modern contemporary architectural design strategy of deriving lesson from traditional houses to extend the period of indoor thermal environment inside the contemporary houses.